2023
DOI: 10.5534/wjmh.220010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes of Clomiphene on Testosterone Levels and Semen Parameters in Subfertile Men

Abstract: Purpose Clomiphene citrate (CC) is prescribed off-label in men to improve testosterone and sperm parameters, but the duration of treatment needed to reach maximal benefit remains unclear. Our objective was to examine temporal effects of CC on total testosterone (TT) and semen analysis (SA) using longitudinal follow-up data in treated men. Materials and Methods We analyzed an IRB-approved database of men treated with CC (25 mg q.d. or 50 mg q.o.d.) from January 2016 thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…However, treatment with CC improved the testosterone levels in obese men with poor sperm concentration. This was in accordance with previous studies that reported improvements in semen parameters post-CC treatment [23][24][25]. CC is a selective estrogen receptor modulator (SERM) and blocks the negative feedback loop that estrogen usually exerts on the HPG axis, which in turn stimulates the release of hormones, such as LH and FSH, from the pituitary gland [26].…”
Section: Discussionsupporting
confidence: 92%
“…However, treatment with CC improved the testosterone levels in obese men with poor sperm concentration. This was in accordance with previous studies that reported improvements in semen parameters post-CC treatment [23][24][25]. CC is a selective estrogen receptor modulator (SERM) and blocks the negative feedback loop that estrogen usually exerts on the HPG axis, which in turn stimulates the release of hormones, such as LH and FSH, from the pituitary gland [26].…”
Section: Discussionsupporting
confidence: 92%